The way OLX transformed pre-owned automobile market; an empirical analysis on users’ experience - A P , Shareef; M A, Shakila Banu (Journal of Management and Science, 2022)
OLX, the world renowned web / mobile based classifieds application is one of the leading platforms for buying and selling preowned automobiles. Along with digitalization in all spheres of human life, pre-owned auto marketplace also has taken a digital turn. This paper is an attempt to understand users’ experience with OLX, the leading platform in India that connects buyers and sellers of pre-owned vehicles. The researcher has chosen two wheelers and four wheelers market for the study as they are the commonly bought and sold items via OLX. The survey was undertaken among OLX users with at least one buying or selling experience. The study primarily examines the factors such as price, time taken for completing the deal, number of enquiries made/received and quality of deals on one hand. Secondly it studies the reasons for not choosing second hand dealers offline for selling or buying by users. The study reveals the most important fact that the users are provided with a cheap and best experience with thousands of buyers and sellers connected on their fingertips. They are now able to connect to thousands of buyers and sellers and get rid of unreasonable prices charged by second hand dealers.